Effectiveness of gamified digital interventions in mental health prevention and health promotion among adults: a scoping review - Leona Aschentrup; Pia Anna Steimer; Kevin Dadaczynski; Timothy Mc Call; Florian Fischer; Kamil J. Wrona (BMC, 2024)
Abstract Background Though still a young field of research, gamified digital interventions have demonstrated potential in exerting a favourable impact on health and overall well-being. With the increasing use of the internet and digital devices, the integration of game elements presents novel opportunities for preventing mental disorders and enhancing mental health. Hence, this review aims to assess the effectiveness of gamified interventions focusing on preventing mental disorders or promoting mental health among adults. Methods Based on a scoping review across four databases (MEDLINE, Embase, PsycInfo and Web of Science), 7,953 studies were initially identified. After removing duplicates and screening titles, abstracts and full texts, 16 studies were identified as suitable for inclusion in a narrative synthesis of findings. We included interventional studies encompassing an intervention and a control group aiming to investigate the effectiveness of the use of gamified digital mental health interventions and the use of gamified digital elements. Results Overall, positive effects of gamified interventions on mental health-related outcomes were identified. In particular, beneficial consequences for psychological well-being and depressive symptoms were observed in all studies. However, further outcomes, such as resilience, anxiety, stress or satisfaction with life, showed heterogenous findings. Most game elements used were reward, sensation and progress, whilst the quantity of elements was not consistent and, therefore, no substantiated conclusion regarding the (optimal) quantity or composition of game elements can be drawn. Further, the outcomes, measurements and analyses differed greatly between the 16 included studies making comparisons difficult. Conclusion In summary, this review demonstrates the potential of integrating digital game elements on mental health and well-being with still a great gap of research. A taxonomy is needed to adequately address relevant game elements in the field of mental health promotion and prevention of mental disorders. Therefore, future studies should explicitly focus on the mechanisms of effect and apply rigorous study designs.